2010
DOI: 10.1111/j.1475-1305.2010.00786.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of the Mesh‐Free Random Grid Method for Full‐Field Synthetic Strain Measurements

Abstract: In responding to the needs of the material characterization community, the recently developed mesh‐free random grid method (MFRGM) has been exhibiting very promising characteristics of accuracy, adaptability, implementation flexibility and efficiency. To address the design specification of the method according to an intended application, we are presenting a sensitivity analysis that aids into determining the effects of the experimental and computational parameters characterizing the MFRGM in terms of its perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…In order to simulate imaging sensor noise, the nodal locations are perturbed by random vectors sampled from an appropriate distribution [47]. It has been found that a good approximation of the noise distribution is that of Gaussian distribution [43,47]. 4.…”
Section: Synthetic Modeling Of Crack Propagationmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to simulate imaging sensor noise, the nodal locations are perturbed by random vectors sampled from an appropriate distribution [47]. It has been found that a good approximation of the noise distribution is that of Gaussian distribution [43,47]. 4.…”
Section: Synthetic Modeling Of Crack Propagationmentioning
confidence: 99%
“…The framework assumes a Probability Density Function (PDF) f N that describes the position vector w i of each of the nodes in the field [56,47]. The contribution of the errors of the various sources is propagated through the computational steps involved in the execution of the DSI analysis to the SSCF s y .…”
Section: Probabilistic Crack Detection and Propagation For Full Fieldmentioning
confidence: 99%
“…Decades of advances in force, displacement, and strain measurement techniques in general, and full-field strain measurement techniques in particular, have enabled the collection of very rich data sets from mechanical tests [9][10][11][12][13][14][15][16][17][18][19]. Having acquired these data, an integrated approach that combines experimental with numerical methods to recover the elastic parameters is very prevalent.…”
Section: Outline Of the Inverse Problemmentioning
confidence: 99%
“…The properties as calculated by the compression experiment data are presented in Eqn. (22), with deviations indicating 95% confidence: Using Eqn. (7) we calculated:…”
Section: <Table 1 Placed Near Here>mentioning
confidence: 99%
“…Such techniques are much more convenient than strain gauges or extensometers because of the vastly reduced system complexity and trivial specimen preparation methods. The DSI methodology operates by tracking the kinematic evolution of centroids of marks painted on the surface of each specimen [15][16][17][18][19][20][21][22][23][24][25][26][27][28] as a function of loading increments or frames. The strain calculation is performed directly on the strain tensor, as described in [25], and provides all three components of strain (horizontal, vertical and shear).…”
Section: Introductionmentioning
confidence: 99%